2018
DOI: 10.1080/2000625x.2018.1471927
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot ulcer outcomes from a podiatry led tertiary service in Kuwait

Abstract: Objective: This single-centred study aims to evaluate the incidence, risk factors and treatment outcomes of a podiatry led, evidence-based diabetic foot ulcer (DFU) clinic. Research design and methods: Data from the DFU database and patient electronic health records were retrospectively collected from patients with new DFUs who were referred for treatment to the Department of Podiatry, Dasman Diabetes Institute, Kuwait, from 1 October 2014, to 31 December 2016. Patients were followed-up until healing occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…Several studies have investigated factors related to the healing time of DFU (diabetic foot ulcer). Evidence suggests a possible association between healing time and factors such as HbA 1c , ulcer size, infection, peripheral artery disease, etiology, and longer duration of diabetes [47]. A recent study presented a linear relationship between HbA 1c and the healing rate of diabetic foot ulcers (every 1% increase in baseline HbA 1c resulted in a decrease of wound area healed per day by 0.028 cm 2 , p = 0.02) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated factors related to the healing time of DFU (diabetic foot ulcer). Evidence suggests a possible association between healing time and factors such as HbA 1c , ulcer size, infection, peripheral artery disease, etiology, and longer duration of diabetes [47]. A recent study presented a linear relationship between HbA 1c and the healing rate of diabetic foot ulcers (every 1% increase in baseline HbA 1c resulted in a decrease of wound area healed per day by 0.028 cm 2 , p = 0.02) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the examination of diabetes patients living with DFU involves a wound classification instrument that provides an indication describing whether ulcers pose a risk of limb amputation or not. Wound dressing selection is carried out by considering the wound size, depth, infection status, necrosis, amount of exudate and the condition of the surrounding tissue . DFU treatment is focused on screening for loss of protective tissue, adequate vascular perfusion assessment, debridement, infection management and pressure alleviation .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported multiple limitations; many conference abstracts however were brief and did not outline limitations. The most commonly reported limitation was that of missing data values, 29 examples include failures to record whether glucose values were fasting or random 30 and limited information on diabetes-specific outcome measures such as foot amputation 31 or cause of death in the community following hypoglycaemia or diabetic ketoacidosis. 32 …”
Section: Discussionmentioning
confidence: 99%
“… 27 There were, however, concerns regarding a lack of longitudinal data in certain EHRs and fragmentation of patient data across diverse EHRs. 30 , 31 These data fragmentation and longitudinal concerns were more prominent in US studies, rather than UK studies, which would be expected from the nature of NHS records; however, without a single national EHR there will remain problems, despite all patients having a single national identifier number (NHS number).…”
Section: Discussionmentioning
confidence: 99%